Investigation of bronchiectasis in severe uncontrolled asthma. (8th June 2017) - Dimakou, Katerina; Gousiou, Anna; Toumbis, Michail; Kaponi, Maria; Chrysikos, Serafeim; Thanos, Loukas; Triantafillidou, Christina
Abstract: Introduction: The presence of bronchiectasis in patients with asthma varies in different reports, while a clear aetiological relation has not been precisely established. Objectives: To investigate the presence of bronchiectasis in patients with severe uncontrolled asthma and examine whether they contribute to the severity of asthma. Methods: Patients with severe asthma were prospectively recruited. HRCT of the chest was performed to identify and grade bronchiectasis using the 'Smith' radiology scale. Investigation of the underlying cause was carried out for patients with bronchiectasis in order to exclude aetiologies other than asthma. The Statistical Package for the Social Sciences (SPSS), version 21, was used. Results: Forty patients were studied, 28 women, mean age (±SD) 57.9 years (±12.4). Mean ACT score was 14.2(±4.9). Main symptoms were: wheezing (95%), cough (92%), dysponea (92%) and sputum production (72%). Mean duration of asthma was 16.5(±11.5) years, exacerbations: 4.4(±2.7)/year. In 27 patients (67.5%) bronchiectasis was diagnosed. In nine patients (22.5%) pathogens were cultured in sputum (mainly Pseudomonas aeruginosa, Haemophilus influenzae ). Patients with sputum production and pathogens in sputum cultures had a higher Smith score compared to those without expectoration and without pathogens, respectively ( P = .005, P < .0001). No correlation was found between the extent of bronchiectasis and lung function. The radiological severity of bronchiectasis was correlated with the antibiotic courses/year ( P = .002). Conclusion: Bronchiectasis is common in patients with severe asthma. Sputum production and pathogen isolation in sputum may indicate the presence of bronchiectasis which seems to contribute to the severity of asthma.